Traveling-Wave-Based Fault Location Method for Hybrid Distribution Network Mixed with Three-Phase and Phase to Phase Supply Lines. Issue 1 (November 2020) - Xinyu, Zhang; Yu, Nie; Chuanzong, Zhao; Wei, Du; Yanan, Wang; Zhigang, WANG; Yanbing, LIU
Abstract: In China, a hybrid distribution network mixed with three-phase main lines and phase to phase supply lines can be found in many MV distribution networks due to lower cost of using two lines from three-phase main lines as well as lower cost of phase to phase transformer. For such a hybrid distribution network it is a challenge for traditional fault location techniques. This paper presents a traveling wave fault location method based on double-terminal measurement techniques. The proposed method analyses the traveling wave propagation mechanism of both aerial mode and zero mode components for a fault. The method then determines which mode component is used for the fault location according to fault types. The method has been developed and assessed on a typical distribution network using ATP power network simulation tool. The tests were conducted under various fault scenarios. The results show that zero mode component is more effective for a fault on the phase of three-phase main lines which is not linked to the phase to phase supply lines. However for a phase-to-phase fault, aerial mode component is more effective. For the remaining fault types, either aerial or zero mode component can be used.